Evaluación de la composición corporal posterior al confinamiento de COVID-19 en futbolistas profesionales - Zurita, Y.; Gracia, M. (Universidad Católica de Santiago de Guayaquil, 2021)
Introduction: The global coronavirus pandemic 2019 (COVID-19) caused a widespread interruption of daily activities as a direct measure to curb infection rates. Athletes like the rest of the world population were affected by measures of social isolation. This problem had a great impact on elite athletes. Anthropometry is a widely used resource at the sports level to evaluate their body composition and the athletic potential of each athlete to assess interventions by the medical and technical staff to optimize sports performance. Objective: to evaluate the body composition after the confinement of COVID-19 in elite soccer players. Methods: a group of 30 professional players of the series A was evaluated after returning from confinement (May 2020) their body composition by means of anthropometry under the labeling protocol recommended by the International Society for the Advancement of Kineatropometry (ISAK). The collected data were analyzed by the SPSS v26.0 program. Results: differences were found between the playing positions and their body composition, especially in the iliac and abdominal crest folds of the shuttlecocks. They present differences in the somatotype, their endomorphy and mesomorphy being moderate, unlike the rest of the establishment. Conclusions: anthropometry is an easy and quick method to apply to know the body composition of athletes. All the players returned from confinement with an optimal sum of folds and with a balanced mesomorphic somatotype, except for the shuttlecocks, which are categorized as endo-mesomorphs.